Relationship of human capital, service delivery and organizational performance: examining the moderating effect of organizational culture in Malaysian government ministries / Muhammad Majid - Majid, Muhammad (2017)
The main purpose of this study was to investigate the relationship between human capital and service delivery with organizational performance of Malaysian government ministries. The study further examined the influence of human capital, service delivery on organizational performance of Malaysian government ministries. Finally the study looked into the moderating effect of organisational culture on the relationship between human capital and organizational performance as well as between service delivery and organisational performance. The data was collected based on the self-administered questionnaire from 432 officers of the selected ministries in the administrative city of Putrajaya, Malaysia. Descriptive statistics, confirmatory factor analysis (CFA), hierarchical multiple regression and Structural Equation Model (SEM) in AMOS were used to analyse the data collected in this study. As hypothesised, the results revealed that human capital and service delivery were significantly and positively related to organisational performance. It was also found that human capital and service delivery has influenced significantly on organizational performance. Apart from that, the study discovered that service delivery has indicated more or higher influence than human capital on organizational performance. Findings in this study correspondingly support that organizational culture moderates the relationship between human capital and organizational performance as well as between service delivery and organisational performance. It was ascertained that organizational culture has moderated the relationship between overall human capital and service delivery with organisational performance.